Pengaruh Kepuasan Kerja, Budaya Organisasi, dan Profesionalisme terhadap Komitmen Organisasi Guru di Yayasan Al-Zahidiyah Kecamatan Geger Kabupaten Bangkalan - Sahid Sahid; Nelud Daraajatul Aliyah; Didit Darmawan (Departement of Mathematics Education, 2024)
In an effort to improve the quality of education, teacher involvement and commitment need to be considered. Job satisfaction and organizational culture can be factors that influence teacher organizational commitment. This research aims to identify and analyse the influence of job satisfaction and organizational culture on teacher organizational commitment at the Al Jahidiyah Foundation, Geger District, Bangkalan Regency. The population of this study was all teachers at the Al Zahidiyah Foundation, Geger District, Bangkalan Regency, totaling 33 teachers. The analysis technique is multiple linear regression. The results show that job satisfaction and organizational culture have a significant role in forming teachers' organizational commitment. This shows that the higher the level of teacher job satisfaction, the higher their level of organizational commitment. Apart from that, organizational culture also has a positive and significant influence on teacher organizational commitment. The implication is that teachers who perceive a positive organizational culture tend to have higher levels of organizational commitment. These factors mutually strengthen their influence on organizational commitment. Therefore, increasing job satisfaction and establishing a positive organizational culture can increase organizational commitment, contributing to improving the quality of education.